2019
DOI: 10.3390/microorganisms7040094
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Single Phage Suspensions and Phage Cocktail in the Inactivation of Escherichia coli and Salmonella Typhimurium: An In Vitro Preliminary Study

Abstract: Enterobacteriaceae Escherichia coli and Salmonella enterica serovar Typhimurium strains are among the main pathogens responsible for moderate and serious infections at hospital and community environments, in part because they frequently present resistance to antibiotics. As the treatment of Enterobacteriaceae infections is empiric, using the same antibiotics to treat E. coli and Salmonella infections, the same concept can be applied with phages. The use of different phages combined in cocktails, frequently use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 87 publications
5
37
0
Order By: Relevance
“…In addition, this finding was consistent with earlier reports that phage av-08 (unknown taxonomy) was able to decontaminate S. Montevideo and STEC O157:H7 on chicken skin [14]. Costa et al [15] also found that single phage ELY-1 or phSE-5 (unknown taxonomy) reduced number of non-O157 E. coli and S. Typhimurium ATCC13311 in a mixture, although this reduction was less than produced by a cocktail of both of these phages in broth culture. The relative contribution of polyvalent phages vs phage cocktails to bacterial biocontrol remains unclear.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, this finding was consistent with earlier reports that phage av-08 (unknown taxonomy) was able to decontaminate S. Montevideo and STEC O157:H7 on chicken skin [14]. Costa et al [15] also found that single phage ELY-1 or phSE-5 (unknown taxonomy) reduced number of non-O157 E. coli and S. Typhimurium ATCC13311 in a mixture, although this reduction was less than produced by a cocktail of both of these phages in broth culture. The relative contribution of polyvalent phages vs phage cocktails to bacterial biocontrol remains unclear.…”
Section: Discussionsupporting
confidence: 92%
“…The emergence of phage-resistant bacterial mutants is a major concern in phage therapy [9,13,38], and this drawback has been overcome through different strategies. Mateus et al [11], Costa et al [14] and Hooton et al [39] found that the emergence of phage-resistance in different bacteria can be prevented by using bacteriophage cocktails. Lopes et al [13] reported that combined treatment with phages and antibiotics is effective in preventing the emergence of phage-resistance in Escherichia coli.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also described new phages active against Psa [7,8], but only a few studies have evaluated the therapeutic potential of phages in controlling this phytopathogen [9,10]. No studies with phage cocktails, or with combined therapies including phages, have yet been evaluated against Psa; approaches that, besides increasing the effectiveness of the treatment, prevent the development of bacterial resistance to phages [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Efficiency of plating (EOP) was determined as described previously [35,38]. Test bacterial strains were grown overnight at 37 • C and 100 µL of each of the test bacterial cultures was used in double layer assays together with 100 µL of 10 6 -10 9 -fold diluted phage lysate.…”
Section: Efficiency Of Platingmentioning
confidence: 99%